2012
DOI: 10.5513/jcea01/13.2.1053
|View full text |Cite
|
Sign up to set email alerts
|

Fruit quality of dog rose seedlings (Rosa canina L)

Abstract: SažetakPasja ruža (Rosa canina L) jedna je od najraširenijih samoniklih pripadnika roda Rosa u našoj zemlji, te prilično zastupljena u prirodnim, ruralnim pa i urbanim područjima. Iako se u svijetu pasja ruža proučava, uzgaja i oplemenjuje, u Hrvatskoj njezin uzgoj gotovo i ne postoji. U prirodi se mogu uočiti velike razlike među biljkama, posebno s obzirom na veličinu plodova, često i na vrlo malim staništima. Istraživanje je provedeno na 8 grmova pasjih ruža na oko 1 ha zapuštene poljoprivredne površine poku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…genotypes BEN CHEIKH-AFFENE et al (2013) reported that fruit mass varied from 0.90 to 1.90 g. ERSOY and ÖZEN (2016) determined that the average fruit mass of Rosa spp. genotypes ranged from 1.40 to 2.77 g. In Montenegro (Bijelo Polje region) ŠEBEK et al (2019) reported that fruit mass of Rosa canina L ranged from 1.25 to 2.76 g. According to ŠINDRAK et al (2012) the average fruit mass of eight Rosa canina seedlings ranged from 1.88 to 2.96 g. Obtained values in this study are in agreement or are slightly lower than the ones obtained in other countries. These results also indicate a large variation of this trait with a notable influence of environmental factors.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…genotypes BEN CHEIKH-AFFENE et al (2013) reported that fruit mass varied from 0.90 to 1.90 g. ERSOY and ÖZEN (2016) determined that the average fruit mass of Rosa spp. genotypes ranged from 1.40 to 2.77 g. In Montenegro (Bijelo Polje region) ŠEBEK et al (2019) reported that fruit mass of Rosa canina L ranged from 1.25 to 2.76 g. According to ŠINDRAK et al (2012) the average fruit mass of eight Rosa canina seedlings ranged from 1.88 to 2.96 g. Obtained values in this study are in agreement or are slightly lower than the ones obtained in other countries. These results also indicate a large variation of this trait with a notable influence of environmental factors.…”
Section: Resultssupporting
confidence: 82%
“…In Romania Rosa canina genotypes obtained a shape index values between 1.16 and 1.72 (GHIORGHIŢĂ et al, 2012b). ŠINDRAK et al (2012) reported significant difference between fruit shape index values of eight Rosa canina seedlings which ranged from 1.48 to 1.86. The values obtained in this study are comparable to the values obtained in other studies.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations